Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
To solve for the values of [tex]\( A \)[/tex] and [tex]\( B \)[/tex] for the partial fraction decomposition of the given function, we follow these steps:
1. Given Expression: We start with the fraction:
[tex]\[ \frac{x}{x^2 - 5x + 6} \][/tex]
2. Factor the Denominator: The denominator [tex]\( x^2 - 5x + 6 \)[/tex] factors into:
[tex]\[ x^2 - 5x + 6 = (x - 2)(x - 3) \][/tex]
3. Set up the Partial Fractions: We express the fraction as a sum of partial fractions with unknown coefficients [tex]\( A \)[/tex] and [tex]\( B \)[/tex]:
[tex]\[ \frac{x}{(x-2)(x-3)} = \frac{A}{x-2} + \frac{B}{x-3} \][/tex]
4. Combine the Fractions on the Right-Hand Side: To combine the fractions, we write:
[tex]\[ \frac{A}{x-2} + \frac{B}{x-3} = \frac{A(x-3) + B(x-2)}{(x-2)(x-3)} \][/tex]
5. Set the Numerators Equal: Since the denominators are the same, we can equate the numerators:
[tex]\[ x = A(x-3) + B(x-2) \][/tex]
6. Expand the Right-Hand Side: Distribute [tex]\( A \)[/tex] and [tex]\( B \)[/tex]:
[tex]\[ x = Ax - 3A + Bx - 2B \][/tex]
7. Combine Like Terms: Combine the terms involving [tex]\( x \)[/tex]:
[tex]\[ x = (A + B)x - 3A - 2B \][/tex]
8. Set up a System of Equations: For the equation [tex]\( x = (A + B)x - 3A - 2B \)[/tex] to hold for all [tex]\( x \)[/tex], the coefficients on both sides must be equal. This gives us two simultaneous equations:
[tex]\[ A + B = 1 \][/tex]
[tex]\[ -3A - 2B = 0 \][/tex]
9. Solve the System of Equations:
- From the first equation, solve for [tex]\( A \)[/tex]:
[tex]\[ A = 1 - B \][/tex]
- Substitute [tex]\( A = 1 - B \)[/tex] into the second equation:
[tex]\[ -3(1 - B) - 2B = 0 \][/tex]
- Simplify and solve for [tex]\( B \)[/tex]:
[tex]\[ -3 + 3B - 2B = 0 \][/tex]
[tex]\[ 3B - 2B = 3 \][/tex]
[tex]\[ B = 3 \][/tex]
- Substitute [tex]\( B = 3 \)[/tex] back into [tex]\( A = 1 - B \)[/tex]:
[tex]\[ A = 1 - 3 \][/tex]
[tex]\[ A = -2 \][/tex]
Thus, the values of [tex]\( A \)[/tex] and [tex]\( B \)[/tex] are:
[tex]\[ A = -2 \quad \text{and} \quad B = 3 \][/tex]
Therefore, the correct answer is:
[tex]\[ (-2, 3) \][/tex]
1. Given Expression: We start with the fraction:
[tex]\[ \frac{x}{x^2 - 5x + 6} \][/tex]
2. Factor the Denominator: The denominator [tex]\( x^2 - 5x + 6 \)[/tex] factors into:
[tex]\[ x^2 - 5x + 6 = (x - 2)(x - 3) \][/tex]
3. Set up the Partial Fractions: We express the fraction as a sum of partial fractions with unknown coefficients [tex]\( A \)[/tex] and [tex]\( B \)[/tex]:
[tex]\[ \frac{x}{(x-2)(x-3)} = \frac{A}{x-2} + \frac{B}{x-3} \][/tex]
4. Combine the Fractions on the Right-Hand Side: To combine the fractions, we write:
[tex]\[ \frac{A}{x-2} + \frac{B}{x-3} = \frac{A(x-3) + B(x-2)}{(x-2)(x-3)} \][/tex]
5. Set the Numerators Equal: Since the denominators are the same, we can equate the numerators:
[tex]\[ x = A(x-3) + B(x-2) \][/tex]
6. Expand the Right-Hand Side: Distribute [tex]\( A \)[/tex] and [tex]\( B \)[/tex]:
[tex]\[ x = Ax - 3A + Bx - 2B \][/tex]
7. Combine Like Terms: Combine the terms involving [tex]\( x \)[/tex]:
[tex]\[ x = (A + B)x - 3A - 2B \][/tex]
8. Set up a System of Equations: For the equation [tex]\( x = (A + B)x - 3A - 2B \)[/tex] to hold for all [tex]\( x \)[/tex], the coefficients on both sides must be equal. This gives us two simultaneous equations:
[tex]\[ A + B = 1 \][/tex]
[tex]\[ -3A - 2B = 0 \][/tex]
9. Solve the System of Equations:
- From the first equation, solve for [tex]\( A \)[/tex]:
[tex]\[ A = 1 - B \][/tex]
- Substitute [tex]\( A = 1 - B \)[/tex] into the second equation:
[tex]\[ -3(1 - B) - 2B = 0 \][/tex]
- Simplify and solve for [tex]\( B \)[/tex]:
[tex]\[ -3 + 3B - 2B = 0 \][/tex]
[tex]\[ 3B - 2B = 3 \][/tex]
[tex]\[ B = 3 \][/tex]
- Substitute [tex]\( B = 3 \)[/tex] back into [tex]\( A = 1 - B \)[/tex]:
[tex]\[ A = 1 - 3 \][/tex]
[tex]\[ A = -2 \][/tex]
Thus, the values of [tex]\( A \)[/tex] and [tex]\( B \)[/tex] are:
[tex]\[ A = -2 \quad \text{and} \quad B = 3 \][/tex]
Therefore, the correct answer is:
[tex]\[ (-2, 3) \][/tex]
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.